Anthurium rosselianum (Araceae), a new species of Anthurium section Belolonchium from Colombia - Croat, Thomas B. (Phytotaxa, 2019)
A new species of Anthurium section Belolonchium from Colombia is described and justified by making comparisons with several other species in the section. The species is named in honor of the late, Allan Rossel, formerly a Volunteer Research Associate with the Missouri Botanical Garden.